FAKTOR-FAKTOR DOMINAN BUDAYA KESELAMATAN DI SEKTOR TAMBANG BATUBARA : KAJIAN LITERATUR - Stevianingrum, Andhika; Erwandi, Dadan (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Safety culture is a combination and reflection of the behavior, beliefs, perceptions and values ??that are shared among workers, management and companies in relation to safety. In the coal mining sector, the formation of a safety culture occurs due to various influencing factors within the company and organization. The purpose of this study is to determine the dominant factors that influence the formation of a safety culture in the coal mining sector. This study is a systematic review using the Preferred Reporting Items for Systematic Reviews & Meta Analyses (PRISMA) method. The databases used in searching the data are Science Direct and Google Schoolar. The keywords used are safety culture, coal mining, safety culture factor, management commitment by producing articles relevant to the purpose of the literature study as many as 8 publications were reviewed. Based on research using the systematic literature review (SLR) method, it was found that there are differences in the causes of the formation of a safety culture. A total of 8 articles on the development of safety culture in the coal mining sector describe the various factors that cause the formation of a safety culture. There are many factors that influence the formation of a safety culture. namely management commitment, employee involvement, knowledge and competence, communication, compliance, and behavior. The six factors are categorized into four interrelated structural components of safety culture, namely safety values, safety leadership, safety attitudes, and safety performance. This systematic study found that these causal factors are divided into dominant and non-dominant factors, each of which has a different effect.